2017
DOI: 10.1080/10926488.2017.1384275
|View full text |Cite
|
Sign up to set email alerts
|

Shy individuals’ interpretations of counterfactual verbal irony

Abstract: Counterfactual verbal irony, an evaluative form of figurative language wherein a speaker's intended meaning is opposite to the literal meaning of his or her words, is used to serve many social goals. Despite recent calls for theoretical accounts to include the factors that influence irony interpretation (Gibbs & Colston, 2012), few studies have examined the individual differences that may impact verbal irony interpretation. The present study examined whether adults with elevated shyness would generate more neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…& Lee 2004; Milanowicz & Kałowski, 2016) and age/developmental period (Banasik-Jemielniak, 2013;Banasik-Jemielniak, 2019;Banasik-Jemielniak & Bokus, 2019;Bosco & Bucciarelli, 2008;Harris & Pexman, 2003;Pexman et al, 2005;Recchia et al, 2010). Recently, emphasis is being placed on personality factors, for example, anxiety or shyness (Gucman, 2016;Milanowicz et al, 2017;Mewhort-Buist & Nilsen, 2017), cheerfulness (Bruntsch & Ruch, 2017a), or various dispositions towards humor (Bruntsch et al, 2016), among others (Kreuz & Johnson, 2020).…”
Section: It Emphasizes Quantitative Measurement and Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…& Lee 2004; Milanowicz & Kałowski, 2016) and age/developmental period (Banasik-Jemielniak, 2013;Banasik-Jemielniak, 2019;Banasik-Jemielniak & Bokus, 2019;Bosco & Bucciarelli, 2008;Harris & Pexman, 2003;Pexman et al, 2005;Recchia et al, 2010). Recently, emphasis is being placed on personality factors, for example, anxiety or shyness (Gucman, 2016;Milanowicz et al, 2017;Mewhort-Buist & Nilsen, 2017), cheerfulness (Bruntsch & Ruch, 2017a), or various dispositions towards humor (Bruntsch et al, 2016), among others (Kreuz & Johnson, 2020).…”
Section: It Emphasizes Quantitative Measurement and Comparisonmentioning
confidence: 99%
“…For example, Costa et al (2001) have reported that women exhibited greater neuroticism than men across cultures (see also Schmitt et al 2008, for similar results, Hofstede, McCrae 2004, on links between personality traits and national culture dimensions). The negative bias inherent in neuroticism and/or anxiety is, in turn, related to a more negative understanding of verbal irony as more critical or threatening (e.g., Gucman, 2016;Mewhort-Buist & Nilsen, 2017;Milanowicz et al, 2017).…”
Section: Self-presentation Style and Self-esteem As Possible Correlat...mentioning
confidence: 99%
“…The relation between verbal irony comprehension and social functioning may be particularly salient for shy individuals who have been found to interpret irony differently than their nonshy peers. For example, shy individuals view ironic speakers as meaner than do their nonshy peers when these speakers deliver both criticisms (in a school‐aged sample; Mewhort‐Buist & Nilsen, ) and compliments (in an adult sample; Mewhort‐Buist & Nilsen, ). Similarly, 6‐ to 11‐year‐old children who show both social anxiety and shy negative affect demonstrate difficulty in appreciating other sociocommunicative behaviour that relies on mental state understanding, such as faux pas (Banerjee & Henderson, ), with this skill holding a bidirectional relationship with peer relations (Banerjee, Watling, & Caputi, ).…”
Section: Introductionmentioning
confidence: 99%